Practical management of disease-related manifestations and drug toxicities in patients with multiple myeloma - Geraldes, Catarina; Roque, Adriana; Sarmento-Ribeiro, Ana Bela; Neves, Manuel; Ionita, Alina; Gerivaz, Rita; Tomé, Ana; Afonso, Sofia; Silveira, Maria Pedro; Sousa, Patrícia; Bergantim, Rui; João, Cristina (Frontiers in Oncology, 2024)
Multiple myeloma (MM) is a very heterogeneous disease with multiple symptoms and clinical manifestations. MM affects mainly elderly patients and is difficult to manage in the presence of comorbidities, polypharmacy, frailty, and adverse events of disease-targeted drugs. The rapid changes in MM treatment resulting from constant innovations in this area, together with the introduction of numerous new drugs with distinct mechanisms of action and toxicity profiles, have led to increased complexity in the therapeutic decision-making and patent management processes. A careful balance between treatment efficacy and tolerability should be considered for every patient. During treatment, close monitoring of comorbidities, disease-related manifestations, and treatment side effects is recommended, as well as a proactive approach, with reinforcement of information and patient awareness for the early recognition of adverse events, allowing prompt therapeutic adjustments. In this review, we discuss various issues that must be considered in the treatment of MM patients, while giving prac.cal guidance for monitoring, prevention, and management of myeloma-related manifestations and treatment-related toxicities. A considerable number of MM patients are frail, have age-related comorbidities at diagnosis or during the disease, and are likely to experience polypharmacy. Patients treated in real-life clinical practice differ from those included in clinical trials, who are usually younger, with better performance status, and without cardiovascular, renal, or hepatic relevant dysfunction. The available data on the efficacy and safety of new therapeutic agents are relatively scarce in subgroups of patients with specific comorbidities and often fail to adequately capture long-term toxicities. This increasing complexity poses challenges for the medical community treating these patients. The appropriate management of toxicities and comorbidities is essential to avoid treatment discontinuation or dose reduction, and the consequent compromise of treatment efficacy, as well as to optimize patients' quality of life. Below, we describe the adverse events, complications, and comorbidities that are most frequently observed in patients with MM, during treatment with the new therapeutic combination, as well as some recommendations for their approach.